Models of Learning Bahasa applied in High School Level: A Literature Study - Dewi Nur Azizah (Institute of Multidisciplinary Research and Community Service, 2022)
Abstract: Education is the main thing in improving human resources. Education is something that is consciously done to combine the abilities of various aspects of human beings. Education is the most important thing in human life from ancient times to the present. Education is important as an assessment of human destiny in building a better nation in the future. Nation building is not carried out by the previous people, but is carried out by the next generation. Thus, to form a better nation, proper education is needed. Good education is carried out with appropriate and effective learning models so that learning materials can be understood by students. In addition, students must also be equipped with language skills. Because these language skills can be used in social life. Language skills must be obtained optimally so that students can optimize their abilities. This research uses descriptive qualitative research literature study. This research collects data from books or journals that have relevance to the topic of discussion in this study. Keywords: language education, learning models, high school.